HUKUMAN PIDANA PENGAMBILAN PAKSA JENAZAH COVID-19 DI INDONESIA - S, Michelle Angelika; Firmansyah, Yohanes; Wijaya, Hanna; Sylvana, Yana (Jurnal Muara Ilmu Sosial, Humaniora, dan Seni, 2021)
Coronavirus (CoV) is included in severe acute respiratory syndrome (SARS). Coronavirus attacks all parts of the world and causes quite a number of deaths. The funeral process is required to follow the protocol of covid-19 but in fact in Indonesia many face situations where the forced pick-up of bodies is unexpected or confirmed covid-19 by family or local residents. One of the social problems that arise is the forced collection of the body of Covid-19 by the community without paying attention to safety and health protocols. This is dangerous because it can be a source of the spread of COVID-19. This research discusses various violations of the law due to the forcible collection of the body of Covid-19 and the forms of Criminal Liability in Collecting Covid-19 bodies. This research is a qualitative research with literature review that uses 3 kinds of approaches, namely: statute approach, conceptual approach, and case approach. The results of this study reveal that the number of cases of forced pick-up of the bodies of suspected or confirmed covid resulted in the Indonesian National Police issuing a telegram letter to the National Police Chief Number ST / 1618 / VI / Ops.2 / 2020 dated June 5, 2020. Unscrupulous individuals either in groups or individually forcing to take the body of a suspect or confirmed that Covid will be charged with multiple articles, namely; Article 214 KUHP jo, Article 335 KUHP jo, Article 336 KUHP jo, article 93 Law Number 6 Year 2018, whose information has been mentioned in the discussion. Coronavirus (CoV) termasuk ke dalam sindrom pernapasan akut parah (SARS). Coronavirus menyerang seluruh belahan dunia dan menyebabkan cukup banyak kematian. Proses pemakaman jenazah diwajibkan untuk mengikuti protokol covid-19 namun pada kenyataanya di Indonesia banyak menghadapi situasi di mana penjemputan paksa jenazah terduga atau terkonfirmasi covid-19 oleh keluarga atau warga sekitar. Salah satu permasalahan sosial yang muncul adalah penjemputan paksa jenazah covid-19 oleh masyarakat tanpa memperhatikan protokol keselamatan dan kesehatan. Hal ini menjadi berbahaya dikarenakan dapat menjadi sumber penyebaran COVID-19. Penelitian ini membahas mengenai berbagai pelanggaran undang-undang akibat penjemputan paksa jenazah covid-19 serta bentuk Pertanggungjawaban Pidana Dalam Pengambilan Jenazah Covid-19. Penelitian ini merupakan penelitian kualitatif dengan telaah pustaka yang menggunakan 3 macam pendekatan yaitu: statuta approach, conceptual approach, dan case approach. Hasil penelitian ini mengungkapkan banyaknya kasus penjemputan paksa jenazah terduga atau terkonfirmasi covid mengakibatkan pihak Kepolisian Republik Indonesia mengeluarkan surat telegram Kapolri Nomor ST/1618/VI/Ops.2/2020 tanggal 5  Juni 2020. Oknum-oknum yang dengan sengaja baik secara berkelompok maupun individu memaksa mengambil jenazah terduga atau terkonfirmasi covid akan dijerat dengan pasal berlapis yaitu; pasal 214  KUHP  jo, Pasal 335 KUHP jo, Pasal 336 KUHP jo, pasal 93  UU Nomor 6 Tahun 2018, yang keterangan nya telah disebutkan dalam pembahasan.